2018
DOI: 10.1016/j.vaccine.2018.05.037
|View full text |Cite
|
Sign up to set email alerts
|

‘What have you HEARD about the HERD?’ Does education about local influenza vaccination coverage and herd immunity affect willingness to vaccinate?

Abstract: Background Vaccination protects individuals directly and communities indirectly by reducing transmission. We aimed to determine whether information about herd immunity and local vaccination coverage could change an individual’s vaccination plans and concern about influenza. Methods We surveyed Minnesota residents 18 years during the 2016 Minnesota State Fair. Participants were asked to identify the definition of herd immunity, to report their history of and plans to receive influenza vaccine, to report their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 19 publications
3
50
1
Order By: Relevance
“…Thus, those who cannot be vaccinated against influenza, for instance, due to allergies to vaccine ingredients, such as gelatin or some antibiotics, which often concerns children below the age of 6 months, would also be protected to an extent on the basis of collective resistance (CDC 2018b). Previous studies have shown that the vaccination coverage in a population should range from 33% to 73% to maximize the benefits of collective immunity and to reduce the transmission of influenza viruses (Logan et al 2018;Plans-Rubió 2012). The present report demonstrates that influenza viruses can infect an adult person of any age.…”
Section: Resultssupporting
confidence: 48%
“…Thus, those who cannot be vaccinated against influenza, for instance, due to allergies to vaccine ingredients, such as gelatin or some antibiotics, which often concerns children below the age of 6 months, would also be protected to an extent on the basis of collective resistance (CDC 2018b). Previous studies have shown that the vaccination coverage in a population should range from 33% to 73% to maximize the benefits of collective immunity and to reduce the transmission of influenza viruses (Logan et al 2018;Plans-Rubió 2012). The present report demonstrates that influenza viruses can infect an adult person of any age.…”
Section: Resultssupporting
confidence: 48%
“…It is important that public health workers recognize the uniqueness in the Canadian context as well as the uniqueness of the family context in predicting speed and likelihood of vaccination. Understanding families' current intentions to vaccinate for SARS-CoV-2 will allow policymakers and public health officials to develop targeted messaging campaigns to those with the greatest degree of vaccine hesitancy (see e.g., [74], [75]). Careful planning for widespread COVID-19 vaccination should begin now [2] so that, when a vaccine is developed, public health information can be disseminated in a targeted manner.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of university students, more than 70% of unvaccinated respondents agreed that receiving information about protecting vulnerable individuals would make them more likely to receive the influenza vaccine, and a recent survey in Minnesota showed that educating respondents who were not previously knowledgeable about herd immunity increased their willingness to receive influenza vaccine. 22,23 Nuanced messaging that focuses on the benefits of protecting people close to adult patients warrants additional investigation in controlled studies as a potential strategy to increase vaccine uptake.…”
Section: Resultsmentioning
confidence: 99%